2015
DOI: 10.3109/01612840.2015.1022843
|View full text |Cite
|
Sign up to set email alerts
|

Moral Decision-Making among Assertive Community Treatment (ACT) Case Managers: A Focus Group Study

Abstract: The context of care in assertive community treatment (ACT) can be precarious and generate ethical issues involving the principles of autonomy and paternalism. This focus group study examined case managers' situated accounts of moral reasoning. Our findings show how they expressed strong moral obligation towards helping the clients. Their moral reasoning reflected a paternalistic position where, on different occasions, the potential benefits of their interventions would be prioritised at the expense of protecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
4
1
Order By: Relevance
“…Interestingly, a prior study found that patients subject to CTOs in Norwegian ACT teams were more satisfied than patients without CTOs [ 58 ]. Our respondents’ overall positive view of ACT stands in contrast to some other studies describing concerns relating to paternalism, rights to privacy and self-determination and human rights [ 59 – 61 ].…”
Section: Discussioncontrasting
confidence: 96%
“…Interestingly, a prior study found that patients subject to CTOs in Norwegian ACT teams were more satisfied than patients without CTOs [ 58 ]. Our respondents’ overall positive view of ACT stands in contrast to some other studies describing concerns relating to paternalism, rights to privacy and self-determination and human rights [ 59 – 61 ].…”
Section: Discussioncontrasting
confidence: 96%
“…ACT case managers’ everyday work takes place in a less predictable healthcare setting compared to work in traditional psychiatric hospital wards and office‐based outreach services. This requires them to work with high levels of initiative and independent decision‐making (Lerbæk et al ; Williamson ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has described how management of physical health issues in the context of some mental health services entails dilemmas, which might lead to MHCPs resorting to deviant practices, such as bending clinical guidelines and omitting certain tasks, in order to safeguard fragile relationships with mental health service users [ 19 , 20 ]. Different factors can lead to such deviant practices.…”
Section: Discussionmentioning
confidence: 99%
“…This duality promotes siloed organisational structures in health care and fragmentation of services across healthcare systems [ 18 ], which create barriers to the promotion of physical health, detection and treatment of coexisting mental and physical illnesses. Consequently, in some mental health care settings the management of physical health issues is marginalised as a strategy to safeguard tenuous clinical relationships or to manage dilemmas embedded in health promoting activities [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%